2012
DOI: 10.1007/s13399-011-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of biomass gasification in a dual fluidized bed gasifier

Abstract: Biomass gasification with steam in a DFBG (dual fluidized bed gasifier) was simulated with ASPEN Plus. From the model, the yield and composition of the syngas, and the contents of tar and char can be calculated. The model has been evaluated against the experimental results measured on a 150 KWth MIUN (Mid Sweden University) DFBG. The model predicts that the content of char transferred from the gasifier to the combustor decreases from 22.5 wt. % of the dry and ash-free biomass at gasification temperature 750• C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 13 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Analyzing the behavior of temperature as a dependent variable with the growth in the amount of steam in the reactors, it is observed that the increase of the steam to biomass ratio leads to a decrease of the gasification temperature [34], as evidenced in Figure 10 for the two biomasses. This is due to the fact that the rise in water favors the formation of H 2 .…”
Section: Gasifier Temperaturementioning
confidence: 95%
“…Analyzing the behavior of temperature as a dependent variable with the growth in the amount of steam in the reactors, it is observed that the increase of the steam to biomass ratio leads to a decrease of the gasification temperature [34], as evidenced in Figure 10 for the two biomasses. This is due to the fact that the rise in water favors the formation of H 2 .…”
Section: Gasifier Temperaturementioning
confidence: 95%
“…The sludge dryer consists of a stoichiometric reactor, DRYR-S, to convert some weight of sludge to water, vaporize it, and then a flash operation, DRYR-FLS, to separate the vapor from dry solids, in similar fashion to [74], [71]. DRYR-S is specified as adiabatic with an exhaust vapor fraction of unity.…”
Section: Dryermentioning
confidence: 99%
“…The main advantages are that the gasifier can easily process various solid fuels, including high moisture biomass, and that the biomass pre-treatment is fairly simple (Zhang 2010). The details can be found in the literature (Göransson et al 2011;He et al 2012). A detailed study on syngas cleaning was made by Göransson et al (2011).…”
Section: Bigcc and Its Implementation In A Tmp Millmentioning
confidence: 99%
“…Table 2. Model input data (Göransson et al, 2011;He et al, 2012 100 bar and 565C 100 bar to 0.6 bar (through a steam turbine cycle) Steam (PM)…”
Section: Simulation With Aspen Plusmentioning
confidence: 99%